2010
DOI: 10.1111/j.1365-2990.2009.01030.x
|View full text |Cite
|
Sign up to set email alerts
|

Population variation in oxidative stress and astrocyte DNA damage in relation to Alzheimer-type pathology in the ageing brain

Abstract: These findings suggest that the changes in oxidative stress and the astrocyte DNA damage response are not accounted for as an accumulating effect due to established Alzheimer-type pathology. We hypothesize that astrocyte damage, leading to impaired function, may contribute to the development of ageing brain pathology in some individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
86
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(93 citation statements)
references
References 53 publications
4
86
0
1
Order By: Relevance
“…End joining activity and protein levels of DNAPKcs are reduced in the midfrontal cortex of patients with AD (4). Similarly, a decrease of DNA-PKcs expression, although not significant, was observed in neurons and astrocytes of temporal cortices of AD cases with increasing Braak stages (42). Taken together, these results enable us to hypothesize that during AD pathology continuous accumulation of A␤ and ROS production would impair DNA-PK activity contributing to neurodegeneration through the inhibition of DNA-PK-mediated DSB repair pathway.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…End joining activity and protein levels of DNAPKcs are reduced in the midfrontal cortex of patients with AD (4). Similarly, a decrease of DNA-PKcs expression, although not significant, was observed in neurons and astrocytes of temporal cortices of AD cases with increasing Braak stages (42). Taken together, these results enable us to hypothesize that during AD pathology continuous accumulation of A␤ and ROS production would impair DNA-PK activity contributing to neurodegeneration through the inhibition of DNA-PK-mediated DSB repair pathway.…”
Section: Discussionmentioning
confidence: 60%
“…The amount of end joining activity correlates with the expression of DNA-PKcs and is dependent on DNA-PK catalytic activity (4). In addition, immunohistochemical analysis of AD temporal cortex showed a decrease, although not significant, of DNA-PKcs expression both in neurons and astrocytes with increasing Braak stages (42). Overall, these findings suggest that repair of DNA DSBs may be deficient in AD, although the molecular candidate causing the NHEJ impairment has yet to be identified.…”
mentioning
confidence: 60%
“…The level of H2AX in astrocytes and neurons was found to significantly decrease with the age of participants (Simpson et al, 2010). Meanwhile, the incidence of endogenous gamma-H2AX foci was increased with age (Sedelnikova et al, 2008).…”
Section: Phosphorylationmentioning
confidence: 82%
“…DNA-PK is required for the NHEJ pathway of DNA repair, whereas, 8-OHdG indicates DNA lesion caused by oxidative damage. Simpson and his colleagues found that the localization of H2AX and DNA-PK demonstrated a good correlation, whereas 8-OHdG localization expression demonstrated a weak correlation with DNA-PK and no significant correlation with H2AX (Simpson et al, 2010). This indicates that H2AX preferentially detects DSBs and is involved in NHEJ repair.…”
Section: Phosphorylationmentioning
confidence: 96%
“…Analyzing transgenic mouse models and neuronal cell cultures, Aβ has been found to accumulate in mitochondria, resulting in elevated hydrogen peroxide production and decreased cytochrome-c oxidase activity, leading to mitochondrial oxidative damage, mitochondrial dysfunction and reduced energy metabolism [176], and cell death. Importantly, it is well established that in return oxidative stress itself increases the generation of Aβ [177][178][179][180], emphasizing oxidative stress to be an important factor in the pathogenesis of AD.…”
Section: Increased Oxidative Stress and Mitochondrial Dysfunctionmentioning
confidence: 99%